Utilizing Mind-Mapping to Foster Career Exploration of High School Students - Silvianingsih Silvianingsih; I Nyoman Sudana Degeng; Triyono Triyono; Carolina Ligya Radjah (Journal of Educational and Learning Studies, 2019)
This study aims to determine the effect of mind-mapping to enhance high school’s student career exploration in guidance group setting. This study use a single subject design with multiple baseline across subject models. The subjects of this study are eight (8) high school students in 10th grade. The data collection instruments in this study are the recording frequency of career exploration (sub components narrowing choices, specifies a vocational choice, and deciding an action implementation), career exploration skill instruments, and treatment instruments in the form of career guidance group guidebooks. The results shows that mind-mapping can be implemented to enhance the students career exploration skill, that is the all subjects’ first sub component exploration skills (narrowing choices) in group data shows average baseline 13.27 increased to 30.86; the second sub component (specifies a vocational choice) shows average baseline 9.67 increased to 22.18; and the third sub component (deciding an action implementation) shows average baseline 13.42 increased to 20.26. The results affirm that the use of mind-mapping is effective to enhance the exploration skills of high school students.